2023
DOI: 10.3389/fendo.2023.951099
|View full text |Cite
|
Sign up to set email alerts
|

Obesity-associated cardiometabolic complications in polycystic ovary syndrome: The potential role of sodium-glucose cotransporter-2 inhibitors

Abstract: Polycystic Ovary Syndrome (PCOS) is the most common endocrine disorder in reproductive-age women. PCOS is characterized by androgen excess, oligo/anovulation, and polycystic appearance of the ovaries. Women with PCOS have an increased prevalence of multiple cardiovascular risk factors such as insulin resistance, hypertension, renal injury, and obesity. Unfortunately, there is a lack of effective, evidence-based pharmacotherapeutics to target these cardiometabolic complications. Sodium-glucose cotransporter-2 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 141 publications
(215 reference statements)
0
4
0
Order By: Relevance
“…Previous studies have con rmed the impact of SGLT2 inhibitors on PCOS (19,20). It has been shown that in a high androgenemic PCOS model, the SGLT2 inhibitor empagli ozin (EMPA) has been bene cial for obesity and blood pressure reduction (21).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have con rmed the impact of SGLT2 inhibitors on PCOS (19,20). It has been shown that in a high androgenemic PCOS model, the SGLT2 inhibitor empagli ozin (EMPA) has been bene cial for obesity and blood pressure reduction (21).…”
Section: Discussionmentioning
confidence: 99%
“…As SGLT-2 is a sodium-glucose cotransporter, SGLT-2 inhibitors reduce sodium reabsorption in the proximal tubule, 40 which leads to increased sodium delivered to the macula densa, reducing renin release and activating the RAAS. 41 In contrast, some studies have shown that sodium reabsorption is reduced in the proximal tubule and that polyureic natriuretic stimulation induced by SGLT-2 inhibitors activates systemic RAAS in patients with diabetes but does not affect intrarenal RAAS. [42][43][44] Furthermore, no significant changes in plasma aldosterone levels are seen in patients treated with SGLT-2 inhibitors, which may be related to the aldosterone circadian rhythm.…”
Section: Obesity-associated Hypertension Sglt-2 Inhibitors and The Re...mentioning
confidence: 97%
“…Because prior research has shown such tremendous benefits for patients with other medical conditions who are started on an SGLT2 inhibitor, there has been an interest in exploring whether this may be a novel treatment option for patients with PCOS [27][28][29][30]. In this review, we examine the effects of SGLT2 inhibitors on various outcomes in women with polycystic ovary syndrome.…”
Section: Sglt2 Inhibitors In Pcosmentioning
confidence: 99%